Health literacy and adherence to chronic disease management in a primary care center - Cieza-Arámbulo, Luis Fernando (2022)
Objective. To evidence the relationship between the degree of health literacy and adherence to the treatment of chronic diseases in a primary care center. Methods. Cross-sectional-analytic-observational study; 326 patients with a diagnosis of arterial hypertension or diabetes mellitus were taken between December 1, 2020 and March 27, 2021. Questionnaires were applied to measure the level of health literacy, as well as adherence to pharmacological and nonpharmacological treatment. The results were statistically compared with the Chi-square test to evaluate the association between the degree of health literacy and adherence to treatment in patients with arterial hypertension (AHT) and diabetes mellitus (DM). Results. 51.84 % had only AHT, 19.02 % had DM and 29.14 % had both AHT and DM. 69.3 % had sufcient health literacy, while 30.7 % had inadequate health literacy. 25.2 % of patients are adherent to treatment (pharmacological and non- pharmacological), while 74.8 % donot have good adherence to  treatment. Forty-three point nine percent of the patients had good adherence to pharmacological treatment, which was associated with age (sig. = 0.011) and socioeconomic level (sig. = 0.025). Fortynine.7% had good adherence to non- pharmacological treatment and noassociation was found with any sociodemographic characteristic. There was an association between health literacy and adherence to treatment (sig. = 0.011). Conclusions. There is a signifcant relationship between the level of health literacy and adherence to treatment.